Turcologica Upsaliensia : An Illustrated Collection of Essays - Csató, Éva Á.,; Gren-Eklund, Gunilla,; Johanson, Lars,; Karakoç, Birsel, (BRILL, 2021)
The richly illustrated essays in Turcologica Upsaliensia tell the stories of scholars, travellers, diplomats and collectors who made discoveries in the Turkic-speaking world while affiliated with Sweden's oldest university, at Uppsala. The study of Oriental languages, including Turkic, has a long tradition at Uppsala. The first part of the volume tells of famous Uppsala professors who were experts not only in Ottoman and Chaghatay, but also in smaller Turkic languages, and of their high esteem for Turkic culture. It also tells how collectors benefited from the Swedish court's cordial relations with the Ottomans. The second part describes selected manuscripts, art objects and maps, calling readers' attention to the cultural heritage preserved at the University Library, which is also accessible online.